2018
DOI: 10.1038/s41598-018-28489-5
|View full text |Cite
|
Sign up to set email alerts
|

Insects with similar social complexity show convergent patterns of adaptive molecular evolution

Abstract: Eusociality has independently evolved multiple times in the hymenoptera, but the patterns of adaptive molecular evolution underlying the evolution and elaboration of eusociality remain uncertain. Here, we performed a population genomics study of primitively eusocial Polistes (paper wasps), and compared their patterns of molecular evolution to two social bees; Bombus (bumblebees), and Apis (honey bees). This species triad allowed us to study molecular evolution across a gradient of social complexity (Polistes <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…Second, we found significant enrichment of caste-biased genes among those under positive selection in a McDonald-Kreitman test (25% of genes under positive selection are caste-biased, hypergeometric test: P = 0.03). Most of these genes (65%) were up-regulated in queen versus worker abdomens, and include genes that function in reproduction in honey bees (e.g., orthologs of the Drosophila melanogaster genes notch and yolkless), indicating that reproductive function is likely under strong selection, as shown for other eusocial bees with a solitary phase prior to the emergence of workers (60,66).…”
Section: Plasticity Of Developmental Gene Expression Is Predictive Ofmentioning
confidence: 90%
“…Second, we found significant enrichment of caste-biased genes among those under positive selection in a McDonald-Kreitman test (25% of genes under positive selection are caste-biased, hypergeometric test: P = 0.03). Most of these genes (65%) were up-regulated in queen versus worker abdomens, and include genes that function in reproduction in honey bees (e.g., orthologs of the Drosophila melanogaster genes notch and yolkless), indicating that reproductive function is likely under strong selection, as shown for other eusocial bees with a solitary phase prior to the emergence of workers (60,66).…”
Section: Plasticity Of Developmental Gene Expression Is Predictive Ofmentioning
confidence: 90%
“…Finally, we performed pairwise Fisher's exact tests of overlap between these directional gene lists in comparison to the shared background list. This test is commonly used in examinations of the intersection between gene lists (e.g., Amsalem et al, ; Dogantzis et al, ; Rutter et al, ) to determine whether the degree of overlap is greater than might be predicted under a null model. All reported results were significant at an FDR‐corrected p < .05.…”
Section: Methodsmentioning
confidence: 99%
“…The simplest societies in our study are represented by Mischocyttarus basimacula basimacula (Cameron) and Polistes canadensis; wasps in these two genera are all independent nest founders and lack morphological castes (defined as allometric differences in body shape, rather than overall size) or any documented form of lifetime caste-role commitment [48][49][50][51] . They live in small family groups of reproductively totipotent females, one of whom usually dominates reproduction (the queen); if the queen dies she is succeeded by a previously-working individual 21 . As such, these societies represent some of the earliest stages in the major transition, where caste roles are least well defined, and where individual-level plasticity is advantageous for maximising inclusive fitness.…”
Section: Study Speciesmentioning
confidence: 99%
“…The copyright holder for this this version posted December 10, 2020. ; https://doi.org/10.1101/2020.12.08.407056 doi: bioRxiv preprint 4 studies have suggested that the processes regulating different levels of social complexity may be different 17,19,21 . The innovations in social complexity and the shift in the unit of selection (from individual-to group-level 22 ) that accompany the major transition may therefore be accompanied by genomic evolution, throwing into question whether a universal conserved genomic toolkit regulates social behaviours across the spectrum of the major transition 8 .…”
mentioning
confidence: 99%